Local Habitat Filtering Shapes Microbial Community Structure in Four Closely Spaced Lakes in the High Arctic - Marois, Catherine; Girard, Catherine; Klanten, Yohanna; Vincent, Warwick F.; Culley, Alexander I.; Antoniades, Dermot (Frontiers in Microbiology, 2022)
Arctic lakes are experiencing increasingly shorter periods of ice cover due to accelerated warming at northern high latitudes. Given the control of ice cover thickness and duration over many limnological processes, these changes will have pervasive effects. However, due to their remote and extreme locations even first-order data on lake ecology is lacking for many ecosystems. The aim of this study was to characterize and compare the microbial communities of four closely spaced lakes in Stuckberry Valley (northern Ellesmere Island, Canadian Arctic Archipelago), in the coastal margin zone of the Last Ice Area, that differed in their physicochemical, morphological and catchment characteristics. We performed high-throughput amplicon sequencing of the V4 16S rRNA gene to provide inter- and intra-lake comparisons. Two deep (>25 m) and mostly oxygenated lakes showed highly similar community assemblages that were distinct from those of two shallower lakes (<10 m) with anoxic bottom waters. Proteobacteria, Verrucomicrobia, and Planctomycetes were the major phyla present in the four water bodies. One deep lake contained elevated proportions of Cyanobacteria and Thaumarchaeota that distinguished it from the others, while the shallow lakes had abundant communities of predatory bacteria, as well as microbes in their bottom waters that contribute to sulfur and methane cycles. Despite their proximity, our data suggest that local habitat filtering is the primary determinant of microbial diversity in these systems. This study provides the first detailed examination of the microbial assemblages of the Stuckberry lakes system, resulting in new insights into the microbial ecology of the High Arctic.